Integrated Operating Scenario to Achieve 100-Second, High Electron Temperature Discharge on EAST*supported by the National Magnetic Confinement Fusion Science Foundation of China (Nos. 2015GB102000 and 2014GB103000). (May 2016) - Qian 钱, Jinping 金平; Gong 龚, Xianzu 先祖; Wan 万, Baonian 宝年; Liu 刘, Fukun 甫坤; Wang 王, Mao 茂; Xu 徐, Handong 旵东; Hu 胡, Chundong 纯栋; Wang 王, Liang 亮; Li 李, Erzhong 二众; Zeng 曾, Long 龙; Ti 提, Ang 昂; Shen 沈, Biao 飚; et al.
Abstract: Stationary long pulse plasma of high electron temperature was produced on EAST for the first time through an integrated control of plasma shape, divertor heat flux, particle exhaust, wall conditioning, impurity management, and the coupling of multiple heating and current drive power. A discharge with a lower single null divertor configuration was maintained for 103 s at a plasma current of 0.4 MA, q 95 ≈7.0, a peak electron temperature of >4.5 keV, and a central density n e (0)∼2.5×10 19 m −3 . The plasma current was nearly non-inductive ( V loop <0.05 V, poloidal beta ∼ 0.9) driven by a combination of 0.6 MW lower hybrid wave at 2.45 GHz, 1.4 MW lower hybrid wave at 4.6 GHz, 0.5 MW electron cyclotron heating at 140 GHz, and 0.4 MW modulated neutral deuterium beam injected at 60 kV. This progress demonstrated strong synergy of electron cyclotron and lower hybrid electron heating, current drive, and energy confinement of stationary plasma on EAST. It further introduced an example of integrated "hybrid" operating scenario of interest to ITER and CFETR.